(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In today’s modern urban development, the demand for green areas around the world is extremely strong, we can see in the example of the landscape design for the environment of the new and multi-storey buildings that are being built every step of the way. This article also talks about the problems in the landscape design of the theater buildings in the city of Tashkent.